System paradigm as a theoretical basis for strategic economic management in modern conditions - G. B. Kleiner (Управленческие науки, 2023)
In the context of the turbulence of the global and national economy and the growing complexity of the interaction of the Russian economy with the Western world, it is necessary to expand the scope and improve the efficiency of organizations’ strategic management at all levels of the economy. Theoretical substantiation of strategic management, its connection with the theory of organization, the theory of the firm, the theory of industrial development and other theories also taking into account the specifics of the Russian economy are not sufficiently developed. In this regard, the formation of a theoretical and methodological basis for the development and implementation of strategic management of the domestic economy is of particular relevance. The article substantiates the expediency of using the system paradigm as a theoretical and ideological basis for developing goals, methods and means of strategic management of organizations. The essence of the system paradigm is revealed as a set of systemic methods of perception, cognition and transformation of the economy, including economic theory, economic practice, economic policy and economic management. The role of strategic management as a foundation and source of co-evolutionary development of the economic planning system, including strategic, calendar and operational management, is shown. The necessity and development of new types of strategic management based on the subject area’s non-quantitative (qualitative) target characteristics and focused on managing the organization’s value, spiritual and intellectual spheres are substantiated. As a new component of the theoretical basis of strategic management, the theory of systems’ spiral evolution is put forward, synthesizing the concept of linear sequential development of the system. According to this approach, the system is viewed as a change in the dominant value orientations and the concept of cyclic development of the system as the alternation of four phases of the dominance of the object, environment, process and project system’s complexes. The theoretical significance of the presented developments is associated with the evolution and deepening of a systems approach in economic research. The practical value lies in substantiating the feasibility of expanding the scope of strategic management using systemic tools to improve the efficiency and coordination of management at all levels of the economy.